Chipped Veneer Restoration: A Full Digital Workflow Utilizing Intraoral Scanner and Lithium Disilicate CAD/CAM Blocks Material - Ramadhan, Daniyal Lazuardi; Fepiosandi, Radixtio Auzan (Universitas Airlangga, 2024)
Background: Chipped veneers are a typical dental problem that affects both appearance and function. Advances in digital dentistry, particularly intraoral scanning and CAD/CAM technology, have transformed restorative procedures, allowing for quicker, more precise, and least invasive treatments. Purpose: The purpose of this article is to illustrate the use of a comprehensive digital workflow to restore damaged veneer, with a focus on process efficiency and precision. Case: A 32-year-old male patient come to clinic with a chipped veneer on the maxillary lateral incisor. The patient expressed concerns about aesthetics and desired a swift, minimally invasive solution. Clinical examination confirmed the need for restoration without replacing the entire veneer. Case management: The restoration process began with shade guide taking and removing the excess cement in the tooth and gingival management using retraction cord, after the preparation performed intraoral scanning process begin, which provided an accurate digital imprint of the damaged tooth and surrounding dentition. The scan results were used to design the repair with CAD software, assuring the best fit and aesthetics. The restoration was made from lithium disilicate utilizing a chairside milling machine. The veneer piece was polished, treated, and then cemented to the tooth. The whole approach reduced chairside time while producing a useful and appealing result. Conclusion: A full digital method that incorporates intraoral scanning and lithium disilicate milling provides a consistent, efficient, and patient-friendly approach to chipped veneer repair. This case demonstrates the potential for digital dentistry to improve clinical results while lowering procedural complexity.